Preparation of some Thiadiazol compounds 1, 2, 3, 4 derived from Coumarin compounds - Ahmed Ahmed; Ali Abeed (College of Education for Pure Sciences, 2005)
Substituted 1,3,4-thiadiazol are well know to have biological activity agent, and to have important uses in the medical, agriculture and industrial application, Several compounds of this group were synthesized from coumarin derivatives, the structure of the new compounds were established on bases of the elemental analysis , physical and spectral data.